Electronic structure and magnetic exchange interactions of Cr-based van der Waals ferromagnets. A comparative study between CrBr3 and Cr2Ge2Te6. Issue 39 (1st July 2020) - O. Fumega, Adolfo; Blanco-Canosa, S.; Babu-Vasili, H.; Gargiani, P.; Li, Hongze; Zhou, Jian-Shi; Rivadulla, F.; Pardo, Victor
Abstract : Ab initio calculations and high-pressure experiments unveil the microscopic mechanism behind the magnetic properties of two Cr-based van der Waals ferromagnets that have different electronic structure. Abstract : Low dimensional magnetism has been powerfully boosted as a promising candidate for numerous applications. The stability of the long-range magnetic order is directly dependent on the electronic structure and the relative strength of the competing magnetic exchange constants. Here, we report a comparative pressure-dependent theoretical and experimental study of the electronic structure and exchange interactions of two-dimensional ferromagnets CrBr3 and Cr2 Ge2 Te6 . While CrBr3 is found to be a Mott–Hubbard-like insulator, Cr2 Ge2 Te6 shows a charge-transfer character due to the broader character of the Te 5p bands at the Fermi level. This different electronic behaviour is responsible for the robust insulating state of CrBr3, in which the magnetic exchange constants evolve monotonically with pressure, and the proximity to a metal–insulator transition predicted for Cr2 Ge2 Te6, which causes a non-monotonic evolution of its magnetic ordering temperature. We provide a microscopic understanding for the pressure evolution of the magnetic properties of the two systems.